High electric conductivity of liquid crystals formed by ordered self-assembly of nonionic surfactant N, N-bis(2-hydroxyethyl)dodecanamide in water1. Issue 9 (7th March 2015) - Zhang, Yan; Li, Dechun; Li, Yaping; Zhang, Sen; Wang, Meng; Li, Ying
<x xml:space="preserve">Abstract</x> Ordered self-assembly of nonionic surfactant N, N-bis(2-hydroxyethyl)dodecanamide in the presence of water achieved high electric conductivity.